2009
DOI: 10.1007/s00464-008-0308-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety, feasibility, and short-term outcomes of laparoscopically assisted primary ileocolic resection for Crohn’s disease

Abstract: Background Outcomes of laparoscopic resection for ileocecal Crohn's disease have been reported previously in smaller studies, suggesting its short-term advantages over open surgery. This study assessed the safety and recovery parameters in the largest, consecutive, single-institution series to date. Methods Consecutive patients undergoing laparoscopically assisted primary ileocolic resection for Crohn's disease between 1994 and 2006 were identified in an institutional prospectively collected database. Operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 20 publications
5
38
1
Order By: Relevance
“…Stricturcoplasty is a safe alternative to resection in jejuno-ileal CD, including ileocolonic recurrence [24] . Additionally, most of studies reported that laparoscopic surgery for CD is feasible and safe and is associated with a shorter hospital stay and a better shortterm outcome compared with open resection [25][26][27][28] . Laparoscopic surgery is preferred for ileocolonic resections.…”
Section: Discussionmentioning
confidence: 99%
“…Stricturcoplasty is a safe alternative to resection in jejuno-ileal CD, including ileocolonic recurrence [24] . Additionally, most of studies reported that laparoscopic surgery for CD is feasible and safe and is associated with a shorter hospital stay and a better shortterm outcome compared with open resection [25][26][27][28] . Laparoscopic surgery is preferred for ileocolonic resections.…”
Section: Discussionmentioning
confidence: 99%
“…This technique was used in 3 large case series focusing on laparoscopic intestinal resection for CD, where laparoscopic-assisted surgery was preferred and internal vascular sections were limited to a minor group of patients; laparoscopic resection and anastomosis was never mentioned in these patients, although the disease was always operated on in a nonemergent setting. 1214 No consensus is available regarding the technique for intestinal anastomoses in CD, and, to date, no evidence supports the benefit of one particular type of anastomosis over another 15 ; we opted for the side-to-side hand-sewn suture, which is our usual technique for the ileocolic stoma. The advantages of a minimally invasive approach are obvious in CD-dedicated studies (less blood loss, swifter return of bowel function and shortened hospital stay, and improved overall quality of life), 16,17 similar colorectal surgery for cancer, 18 as well as in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] Laparoscopic resection of ileocolic CD appears safe and feasible, with a number of studies reporting conversion in 6%-10% of patients and rates of complication of 10%, most commonly ileus in 4%. The benefits are less scarring, earlier resumption of diet, quicker return of gastrointestinal function, fewer analgesic requirements, and shorter hospital stay.…”
Section: Minimally Invasive Surgery and Complicationsmentioning
confidence: 99%
“…The benefits are less scarring, earlier resumption of diet, quicker return of gastrointestinal function, fewer analgesic requirements, and shorter hospital stay. [50][51] A potential benefit of the laparoscopic approach is to reduce adhesion formation and potentially the incidence of small bowel obstruction and need for further laparotomy in the long term. A single study has reported a small bowel obstruction rate of 11.1% at 5 years following ileocolic resection in patients treated with laparoscopy, compared to 35.4% in patients treated with open surgery.…”
Section: Minimally Invasive Surgery and Complicationsmentioning
confidence: 99%